Electrochemical, quantum chemical, and thermodynamic investigation of a Schiff base corrosion inhibitor for XC70 steel - Abdelbasset Recherache; Fatiha Benghanem; Linda Toukal; Nourelhouda Bounedjar; Malika Foudia; Buzuayehu Abebe; Mir Waqas Alam (Scientific Reports)
Abstract In this paper, a Schiff base, (Z)-2-((3-nitrobenzylidene) amino) phenol (NBAP) was obtained and characterized using proton nuclear magnetic resonance (1H NMR), 13C NMR spectra, Fourier transform infrared spectrophotometer (FT-IR) and element analyses. The corrosion inhibition performance of XC70 steel by NBPA was studied by the potentio dynamic polarization (PDP), electrochemical impedance spectroscopy (EIS) and surface morphology test. The effect of the NBAP concentration and the temperature was studied. The experimental findings revealed the corrosion inhibition efficacy of the Schiff base NBAP on XC70 in 1 M HCl, as indicated by an inhibition effectiveness of 89% at an optimal concentration of 10− 4M.The efficiency of inhibition was seen to rise with rise in inhibitor concentrations and temperature. PDP studies revealed that NBAP behaves as a mixed type of inhibitor. Thermodynamic investigations elucidated the corrosion inhibition’s mechanism. The computed thermodynamic factors, namely ΔG°ads, ΔHa, Ea, and ΔSa, indicate that NBAP significantly inhibits the deterioration of XC70 mild steel in 1 M of HCl by a mechanism of chemisorption, with the process of adsorption adhering to a Langmuir adsorption isotherm. Surface investigation of NBAP using SEM measurements unequivocally validated the establishment of a dense protective coating of the inhibitor on the mild steel surface. Experimental investigations were integrated with theoretical studies employing the Density Functional Theory (DFT) process to examine the anticorrosion efficacy and inhibitory mechanism. A Molecular Dynamics Simulation (DMS) was conducted to investigate the interaction among the inhibitor molecule and the Fe (110) surface. The calculated quantum chemical parameters have shown a strong link with experimental inhibition efficiency. The study exhibits a considerable improvement in corrosion prevention by developing a strong inhibitor that creates a dense layer on mild steel. By combining experimental findings with theoretical frameworks such as Density Functional Theory and Molecular Dynamics Simulation, the study provides a thorough understanding of the inhibitor’s mechanism of action. The link between computed quantum chemical parameters and observed experimental inhibitory efficiency emphasizes the unique approach’s potential for improving the longevity and durability of mild steel in corrosive settings.